1997
DOI: 10.1088/0022-3727/30/17/004
|View full text |Cite
|
Sign up to set email alerts
|

Electron relaxation phenomena on a copper surface via nonlinear ultrashort single-photon photoelectric emission

Abstract: Time-resolved single-photon photoelectric emission measurements from polycrystalline copper, using an autocorrelation system of 450 fs duration at 248 nm laser pulses, are reported. This experimental technique makes possible the direct measurement of the electron energy relaxation time at the surface as well as the evaluation of the electron - phonon scattering time in metallic samples. A nonlinear increase of the electron photocurrent versus the laser intensity is observed. This nonlinearity is attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…The Fowler-DuBridge photoemission model, which was developed in the 1930s, has also successfully predicted photoemission from other materials. 31,32 In the present work, we employ a slightly different adaptation of the Fowler-DuBridge model that incorporates three significant modifications. First, the present formulation emphasizes the similarity between photoemission and thermionic emission; second, it avoids the necessity of using different calculations for cases in which the photon energy is greater than or less than the emitter's work function; and third, the present formulation does not rely on extensive integration approximations that in some situations compromise the precision of results.…”
Section: B Photoemissionmentioning
confidence: 99%
“…The Fowler-DuBridge photoemission model, which was developed in the 1930s, has also successfully predicted photoemission from other materials. 31,32 In the present work, we employ a slightly different adaptation of the Fowler-DuBridge model that incorporates three significant modifications. First, the present formulation emphasizes the similarity between photoemission and thermionic emission; second, it avoids the necessity of using different calculations for cases in which the photon energy is greater than or less than the emitter's work function; and third, the present formulation does not rely on extensive integration approximations that in some situations compromise the precision of results.…”
Section: B Photoemissionmentioning
confidence: 99%
“…[34][35][36][37][38][39] An account of procedures, developed to simulate dispenser photocathodes and metals, 30,40 are summarized here. [34][35][36][37][38][39] An account of procedures, developed to simulate dispenser photocathodes and metals, 30,40 are summarized here.…”
Section: A Heat Diffusion Equationsmentioning
confidence: 99%
“…The electron temperature is designated by T e , the lattice temperature by T i ͑following the notation of Papadogiannis et al 38 ͒. The electron temperature is designated by T e , the lattice temperature by T i ͑following the notation of Papadogiannis et al 38 ͒.…”
Section: A Heat Diffusion Equationsmentioning
confidence: 99%
“…Previously reported multiphoton emission experiments [6][7][8][9][10][11][12][13] have been on metals with work functions of 4 -5 eV and with shorter laser pulse lengths ͑generally 100-450 fs or smaller͒. In most of these studies, the incident photons had energies greater than the work functions of the target metals.…”
mentioning
confidence: 99%
“…The electron temperature may be calculated theoretically using a steady-state approximation to the coupled differential equations governing electron and lattice temperature. 17 It can be shown that…”
mentioning
confidence: 99%